Influence of spinal cord lesion level and severity on H‐reflex excitability and recovery curve. Issue 4 (30th June 2015) - Kumru, Hatice; Albu, Sergiu; Valls‐Sole, Josep; Murillo, Narda; Tormos, Josep Maria; Vidal, Joan
ABSTRACT Introduction Changes in spinal reflexes can result from alterations in the spinal cord and descending pathways. We studied whether H‐reflex excitability and its recovery depend on the level and/or severity of spinal cord injury (SCI). Methods The soleus Hmax and Mmax responses and the H‐reflex recovery curve (HRC) at interstimulus intervals (ISIs) ranging from 50 to 1, 000 ms were recorded in 38 SCI individuals and 18 healthy subjects. Results Amplitude of Mmax correlated with level and severity of lesion (smaller amplitude correlated with more severe SCI or with more caudal lesion). Hmax/Mmax correlated only with age in the SCI group. HRC was increased significantly in complete SCI at ISIs < 500 ms and in incomplete SCI at ISIs > 200 ms with respect to healthy subjects. Conclusions The changes in spinal reflexes as measured by the H‐reflex and its recovery curve after SCI depend on the severity, but not on the level of the lesion. Muscle Nerve 52: 616–622, 2015